Quality of Life of Breast Cancer Patients - Tahshin, Raihana; Kabir, Md Iqbal; Flora, Meerjady Sabrina (Journal of Preventive and Social Medicine, 2021)
Background: Breast cancer control in a low-income country such a Bangladesh is a challenging endeavor influenced by a myriad of forces. Quality of life is now considered an important endpoint in cancer clinical trials. The study was conducted to determine the quality of life of breast cancer patients. Methods: This cross-sectional study was conducted among 142 breast cancer patients. Data were collected by faceto- face interview using European Organization for Research and Treatment of Cancer questionnaire from respondents once only ensuring the privacy, confidentiality and maintaining ethical issues. The study was conducted during the period from January 2012 to June 2012 in National Institute of Cancer Research and Hospital (NICRH), Mohakhali, Dhaka-1212, Bangladesh. Results: The study revealed that majority of the participants were housewife (76.1%) and the maximum were in the 41-50 age groups. Mean age of the respondents was 42.80(±8.95) years. Maximum respondents (30%) had passed SSC and primary educated were 27%. The average monthly income was Tk. 11,570.70. Better income group (Tk. 15,000.00 monthly) enjoy better quality of life than other group. Quality of life was better in women living in joint family rather than nuclear family. Among 142 respondents who heard the name of breast cancer, majority of the respondents heard it from Neighbors/ Relatives. Adequate monthly income (p=0.006) and small size family (p=0.02) improved the quality of life while treatment specific attributes and duration of disease sufferings worsen the quality of life of breast cancer patients Conclusion: The overall QOL score was considerably poor in this study. Early diagnosis with regular follow-up treatment could be a way of improving quality of life among breast cancer patients. JOPSOM 2020; 39(2): 20-33